Blood group determinates incidence for pancreatic cancer in Germany - Pelzer, Uwe; Klein, Fritz; Bahra, Marcus; Sinn, Marianne; Dörken, Bernd; Neuhaus, Peter; Meyer, Oliver; Riess, Hanno (Frontiers in Physiology, 2013)
Background: Genetic risk factors for sporadic pancreatic cancer are largely unknown but actually under high exposure. Findings of correlations between the AB0 blood group system (Chromosome 9q34,1 - q34,2) and the risk of pancreatic cancer (PC) in patients from Asia, America and south Europe have already been published. So far it is unclear, whether this correlation between blood group an PC incidence can be found in German patients as well. Methods: 166 patients who underwent a resection of PC were evaluated in a period between 2000 and 2010. Blood group reference distribution for the German population is given as: 0: 41%; A: 43%, B: 11%; AB: 5%; Rhesus pos: 85%; Rhesus neg: 15%. Analyses were done using the non-parametric Chi²-test (p value two sided; SPSS 19.0). Results: Median age was 62 [34-82] years. Gender: female 73/44%; male: 93/56%. Observed blood group proportions: 0: 43 (25.9%)/ A: 94 (56.6%)/ B: 16 (9.6%)/ AB: 13 (7.8%)/ Rhesus pos.: 131 (78.9%)/ neg.: 35 (21.1%). We detected a significant difference to the German reference distribution of the AB0 system (Chi² 19.34, df 3, p<0.001). Rhesus factor has no impact on AB0-distribution (Chi² 4.13, df 3, p=0.25), but differs significantly from reference distribution – probably due to initial AB0-variation (Chi² 4.82, df 1, p=0.028). The odds ratio for blood group A is 2.01 and for blood group 0 is 0.5. Conclusions: The incidence of PC in the German cohort is highly associated with the AB0-system as well. More patients with blood group A suffer from PC (p<0.001) whereas blood group 0 was less frequent in patients with PC (p<0.001). Thus, our findings support the results from other non-German surveys. The causal trigger points of this carcinogenesis correlation are still not known.